Thyroid peroxidase antibody positivity among euthyroid pregnant women and its association with foeto-maternal outcome - Gulati, Kanika; Sharma, Manjula; Bharti, Rekha; Biswas, Krishna; Batra, Achla; Aggarwal, Abha; Batra, Aruna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Thyroid peroxidase antibody (TPO-Ab) positivity is associated with increased risk of adverse pregnancy outcomes. The present study was planned to find out the prevalence of TPO-Ab and its association with adverse foeto-maternal outcome in euthyroid pregnant women. Methods: A total of 510 euthyroid pregnant women with <20 weeks gestation were recruited from antenatal clinic. Serum TPO-Ab testing was done and women were divided into 2 groups. The study group comprised of TPO-Ab positive women and control group comprised of age and parity matched TPO-Ab negative women, double in number to that of the study group. Repeat Serum TSH was done at term/delivery and women were followed till delivery for foeto-maternal outcome. Results: The prevalence of TPO-Ab positivity in euthyroid pregnant women was 11.3%. A significant number of women in the study group developed hypothyroidism at term/delivery, 18.61% vs 7.61%, respectively, p=0.02. None of the women in the study or control group developed gestational diabetes or placental abruption, or had babies with NND or RDS. There was one IUD in the study group, rest of the maternal and foetal outcomes studied were not statistically significant between two the groups. The caesarean section rates in both groups was not statistically different, however, there were more caesarean sections done for foetal distress in the study group, p=0.04. Conclusions: Thyroid peroxidase positivity is present in 11.3% of euthyroid women and is associated with an increased risk of developing hypothyroidism during pregnancy. It is not associated with adverse foeto-maternal outcome.